«ШӘРИЯР» ДӘСТАНЫНЫҢ КӨРКЕМЛИК АЙРЫҚШАЛЫҚЛАРЫ (Дәстанның тийкарғы идеясы, образлар системасы, сюжетлик-композициялық өзгешеликлери ҳәм көркемлик) - Кеңесбаева, Ш.К. (FAN va JAMIYAT, 2020)
The artistic features of the «Sharyar» epic are extensively analyzed on the example of Utaniyaz and Kulamet jirau options. Thus, every word, every image ingenious composition, every well-chosen artistic form, every means of artistic expression, every large and small detail, which is precisely described in any work of art, is used in its place. Concluded that, it had a role in the induction.